Long-Term Evaluation of Mid-Cost Optical Particle Counters for PM2.5 Monitoring in an Underground Subway Station: Insights from a 15-Month Study - Trieu-Vuong Dinh; Byeong-Gyu Park; Sang-Woo Lee; In-Young Choi; Da-Hyun Baek; Jo-Chun Kim (Chemosensors)
A beta-ray attenuation monitor (BAM) is preferred as a reference instrument for monitoring particulate matter in the air due to its accuracy. However, BAM cannot be used in large numbers for spatial distribution monitoring because of its high investment cost. Thus, a mid-cost optical particle counter (OPC) is an alternative solution for widespread use. However, its long-term performance with respect to various monitoring environments should be taken into account. In this study, six mid-cost OPCs were used to measure PM2.5 concentrations at an underground subway station and compared with a reference BAM over 15 months. OPCs were placed in the waiting space and platforms to compare PM2.5 concentrations and determine PM2.5/PM10 ratios. The reference BAM was installed on the platform. Error analysis revealed a significant discrepancy, with normalized errors exceeding 30%, between the 1-h average PM2.5 concentrations recorded by the BAM and OPCs at the same location. In contrast, the 24-h average PM2.5 concentrations measured by the BAM and OPCs at the same location showed similar patterns, with stronger correlations (r2 = 0.80–0.93) compared to the 1-h averages (r2 = 0.63–0.83). The normalized errors for the 24-h averages ranged from 13.9% to 21.2%, depending on seasonal variations. These findings suggest that OPCs can effectively monitor 24-h average PM2.5 concentrations in an underground subway station over a year without additional calibration, making them a cost-effective option. In addition, 1-h average PM2.5 concentrations varied across different sampling spaces and were influenced by PM2.5/PM10 ratios. Hence, when measuring the 1-h average mass concentration of PM2.5, it is essential to consider PM characteristics and seasons.